Evaluasi Desa Layak Anak di Kabupaten Lampung Selatan (Studi Pada Desa Natar dan Desa Kali Sari) - Indah Kamilia; Novita Tresiana; Simon Sumanjoyo Hutagalung (Jurnal Administrativa, 2020)
Implementation of Child Protection in South Lampung Regency under the Ministry of Women's Empowerment and Child Protection (PPPA) which promotes the Child Friendly Village program. In this study, Natar Village is one of the villages in the Natar District that implements the Child-Friendly Village program and Kali Sari Village as the object comparison village in this study. Evaluation is a form of supervision to determine a program, especially the Child Friendly Village program, whether a village can be categorized as a village worthy of children or not. This can later be used as a recommendation for other villages that do not yet have regulations regarding the properness of children to participate in achieving common goals. The type of research used in this research is descriptive type with a qualitative approach, data collection techniques, observation, interviews, documentation. The results of this study indicate that the Evaluation of the Child-Friendly Village Program in South Lampung Regency shows that the Child-Friendly Village Program has been implemented well, this can be seen from the results of the research which states that the evaluation of the program service process has been carried out as planned, the planned target has been served. The evaluation that has been carried out states that this program has shown good performance and benefits for the community and especially for children.